The Relationship of Learning Effectiveness Factors and Academic Achievement in Dezful University of Medical Sciences Students - Saeed Moshtaghi; Mohammad Afzalzadeh (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: The aim of present study was to examine the applicability of Russell and Petrie theory in prediction of academic achievement by college learning effectiveness inventory (CLEI). Materials and Methods: This correlational study was performed at Dezful University of Medical Sciences, on 245 students (136 men and 109 women), who were selected by random sampling method. Data was collected using the third version of CLEI. The mean scores of students were used as an index for academic achievement. Data were analyzed by descriptive statistics, Pearson correlation coefficient, multiple regression using SPSS 18 software. Results: The results indicated that six factors of college learning effectiveness correlated positively with students' academic achievement. In addition, the factors assessed, according to the study of academic self-efficacy and organization and attention to study factors were strongest predictors of academic achievement. Conclusion: Findings of the study emphasized the importance of investigating different factors based on Russell and Petrie model, and their influence on academic variables.